La Inteligencia Emocional en el aprendizaje de los estudiantes de enfermería en las prácticas clínicas (2023)
The present work entitled: emotional intelligence in the learning of nursing students in clinical practices, had the objective of: Describe Emotional Intelligence in the learning of nursing students in clinical practices; Its methodological design was based on a narrative literature review using the Whittemore and Knafl method taking into account each of its 5 stages: Likewise, the PRISMA flow chart was used. Within the national and international scope, 9 articles in total were obtained, as a result of the different filters that met the inclusion criteria; Likewise, it was possible to simplify, visualize, compare, categorize, analyze and conclude the information clearly; Finally, 2 categories were established in emotional intelligence that are related to coping skills proposed by nursing; The first category was defined as academic ability, which emphasizes the inclusion of EI in the academy from the beginning of the career; The second category is identical as a relational skill that refers to a positive relationship between the teacher and student binomial